Building on shared experiences: The evaluation of a phone-based parent-to-parent support program for helping parents with their child's substance misuse. (January 2020) - Carpenter, Kenneth M.; Foote, Jeffrey; Hedrick, Tom; Collins, Kevin; Clarkin, Sean
Abstract: Aims: To evaluate the feasibility and acceptability of a phone-based parent-to-parent support program, in which parents who have had children with substance use problems provided support and guidance to other parents seeking help about their child's substance misuse. Method: 228 parents completed a 2.5-day coach workshop and 6-months of ongoing training and support in the Invitation to Change Approach (ITC), a program blending evidence-based strategies for addressing substance use disorders. Trained parent coaches provided support and guidance to 278 parents for up to 8 weeks. We evaluated the coach trainees' satisfaction with the training program and pre-post differences in self-care and the use of communication and behavior management strategies among parents who called the helpline. Results: The coach training program was rated as very satisfying, useful, and coaches would recommend the training to other parents. Among parents enrolled in the coaching program, a significantly greater proportion reported improvements on a majority of the survey items (e.g. a decrease in depression and better communication with child). Conclusions: Remote parent-to-parent coaching appears promising for providing emotional and evidence-based informational support to family members parenting a child with substance use problems. Highlights: Parents of a child with a SUD are motivated to provide information and emotional support to other parents. Being trained to provide peer support in the context of evidence-based practices was rated as highly acceptable and useful. Parents receiving peer-to-peer support reported improvements in their emotional distress and the use of helping strategies. Parent-to-parent phone-based coaching can introduce families to evidence-based practices and support.